Volunteer as a Subject of the Security and Defense Sector of Ukraine - Drobina, Inna Oleksandrivna (Global Prosperity, 2023)
The article explores the normative and legal definition of such legal categories as "volunteer," "volunteer assistance," "charitable activity," and "subject of national security and defense of Ukraine." Specific normative acts that recognize the subjectivity of volunteers in the security and defense sector of Ukraine are established. Volunteering in our country is beginning to acquire its characteristic features of development under the influence of historical and cultural traditions, socio-economic and political factors. Currently, volunteering in Ukrainian society is perceived as an important resource for social and economic development, improving the quality of life, and capable of addressing socially significant tasks at the local, regional, and national levels. However, the problem has not been comprehensively addressed, and many aspects of the phenomenon remain understudied. Most often, the focus of authors is on specific aspects of Ukrainian volunteering. The article notes that volunteer assistance to the Armed Forces of Ukraine competes with the military power of the aggressor, military technologies, and undermines all possible military advantages of the enemy. The management of the volunteer movement should be based on principles such as providing necessary resources and information, popularization, humane relations, realism, and mutual assistance. The conclusion is drawn that volunteering in Ukraine has gained significant momentum in modern conditions. Young people, in particular, actively engage in the volunteer movement both within the country and beyond its borders. Young individuals demonstrate a willingness to help others, participate in humanitarian missions, support the military and those affected by conflicts, as well as engage in other types of voluntary activities. It is noted that the unique approach to the normative and legal definition of a volunteer as a subject of the national security and defense sector of Ukraine is a result of the need to utilize the resources of civil society in the face of external threats to the territorial integrity of the Ukrainian state. This approach is not typical for many other countries and represents a unique Ukrainian specificity. It is stated that the formal recognition of a volunteer as a subject of the security and defense sector of Ukraine requires proper normative consolidation. This means that volunteers who contribute to national security and defense should have a legal status that defines their rights, duties, and protection. The normative and legal recognition of volunteers as subjects of the security and defense sector allows them to effectively assist in these areas, ensuring coordination with official structures and maximum impact on the results of their efforts. This approach to the legal recognition of volunteers is a response to the unique challenges faced by Ukraine and reflects the willingness of citizens to help their country in difficult times.